PENGARUH VARIASI KONSENTRASI LIMBAH AIR CUCIAN BERAS DAN VARIASI DOSIS PUPUK NPK TERHADAP TANAMAN CABAI MERAH (Capsicum Annum L.) - Pega, Eusabius Paul; Mariana Teresa Pega; Mitha Rabiyatul Nufus; Rosalia Silaban; Rio Agung Nugroho (Fakultas Pertanian Universitas Janabadra, 2025)
Red chili is widely used as a key ingredient in various traditional dishes. However, its availability often fluctuates due to seasonal changes, pest and disease outbreaks, and distribution challenges, resulting in unstable market prices. This study aims to evaluate the effects of different concentrations of rice washing wastewater and varying dosages of NPK fertilizer on red chili plants (Capsicum annuum L.). It also investigates whether there is a significant interaction between these two treatments on the plant's growth and yield. The research employed a factorial Completely Randomized Design (CRD) with two treatment factors and one control. The first factor was the concentration of rice washing wastewater at three levels: 150 ml/plant, 300 ml/plant, and 450 ml/plant. The second factor was the dosage of NPK fertilizer: 10 g/plant, 15 g/plant, and 20 g/plant. The results indicated a significant interaction between the wastewater and fertilizer treatments on stem diameter at 4 weeks after transplanting and fruit diameter. The best outcome was observed with the application of 450 ml/plant of fermented rice washing water, which significantly improved plant height at 4 weeks, number of fruits, and fruit weight.